Early Mackinac: "the fairy island" : a sketch - Williams, Meade C. (Buschart, 1898)
Name -- Indian legends -- Indian character -- French, English, and American flags -- Old fort -- Military history, and War of 1812 -- Fur trade -- Early village life -- Christian missions and churches -- Natural attractions -- Antiquities.